Low-Frequency Stimulation of Silent Nociceptors Induces Secondary Mechanical Hyperalgesia in Human Skin. (1st September 2018) - Sauerstein, Katja; Liebelt, Jan; Namer, Barbara; Schmidt, Roland; Rukwied, Roman; Schmelz, Martin
Graphical abstract: Highlights: Stimulation of silent nociceptors at low frequency (1/20 Hz) provokes punctate hyperalgesia in human volunteers. Higher frequencies were required to provoke axon reflex erythema (1/5 Hz) or allodynia (1/4 Hz) Low-level discharge in silent nociceptors could sensitize spinal nociceptive processing in neuropathic pain patients. Abstract: Secondary mechanical hyperalgesia to punctate mechanical stimuli and light touch (allodynia) are prominent symptoms in neuropathic pain states. In a combined microneurographic and psychophysical study, we investigated the role of mechano-insensitive (silent) nociceptors regarding induction. Electrical thresholds of mechano-sensitive and silent nociceptors were assessed by microneurography with two closely spaced intracutaneous electrodes (i.c.) and a transcutaneous configuration (t.c.) in the foot dorsum. For t.c. stimulation there was a marked difference between silent (median, quartiles; 60, 50–70 mA, n  = 63) and mechano-sensitive fibers (3, 2–5 mA, n  = 107). In silent fibers, thresholds were lower for i.c. stimulation (16, 14–19 mA, n  = 8), but higher in mechano-sensitive units (6, 5–6 mA, n  = 13). Corresponding psychophysical tests showed no difference between the stimulation configuration for pain thresholds, but lower thresholds for the i.c. stimulation in axon reflex erythema (12 vs. 21 mA), punctate hyperalgesia (9 vs. 15 mA) and allodynia (15 vs. 18 mA). Punctate hyperalgesia was evoked at very low stimulation frequencies of 1/20 Hz (7/7 subjects), whereas the induction of an axon reflex flare required stimulation at 1/5 Hz. Electrical stimulation which is sufficient to excite mechano-insensitive C nociceptors can induce secondary mechanical hyperalgesia even at low frequencies supporting a role of such low-level input to clinical pain states. Thus, differential nociceptor class-specific input to the spinal cord adds to the complexity of modulatory mechanisms that determine nociceptive processing in the spinal cord.